Avocado (Persea americana Mill.) by‐products and their impact: from bioactive compounds to biomass energy and sorbent material for removing contaminants. A review. (1st March 2019) - Colombo, Raffaella; Papetti, Adele
Summary: Avocado industry produces enormous by‐products and represents an important source of raw material in food and non‐food applications. This review aims to focus the attention on the valorisation of avocado wastes recycling to produce different materials with important industrial and environmental impacts. In fact, peels and seeds can be reused in food and cosmetic fields due to the presence of bioactive ingredients such as polyphenols; thanks to their antioxidant and antinflammatory activities. In addition, both peels and seeds can be reused in the production of carbonaceous materials with important consequences for environmental pollution in the removal of contaminants from water. Interesting applications of avocado wastes in photocatalysis and biofuel production are also discussed. All the utilisations attest the great potential of recycling avocado by‐products, a little known resource. Abstract : Utilisation of avocado by‐products.